2010
DOI: 10.1007/s00024-010-0130-0
|View full text |Cite
|
Sign up to set email alerts
|

Damage and Changes in Mechanical Properties of a Gabbro Thermally Loaded up to 1,000°C

Abstract: Thermal loading of rocks at high temperatures induces changes in their mechanical properties. In this study, a hard gabbro was tested in the laboratory. Specimens were slowly heated to a maximum temperature of 1,000°C. Subsequent to the thermal loading, specimens were subjected to uniaxial compression. A drastic decrease of both unconfined compressive strength and elastic moduli was observed. The thermal damage of the rock was also highlighted by measuring elastic wave velocities and by monitoring acoustic emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 24 publications
4
53
0
2
Order By: Relevance
“…We see a clear correlation of crack area per unit volume (Sv) to the observed compressional wave velocities ( Figure 8D) and interpret this to be attenuation of the compressional wave through the cracked intracrystalline and intercrystalline boundaries that are abundant in the andesite (e.g., Figures 3 and 4). Many authors (e.g., Vinciguerra et al 2005;Keshavarz et al 2010;Blake et al 2012; Heap et al 2014) have also shown that the elastic wave velocities can be highly attenuated by the presence of microcracks.…”
Section: Micromechanical Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…We see a clear correlation of crack area per unit volume (Sv) to the observed compressional wave velocities ( Figure 8D) and interpret this to be attenuation of the compressional wave through the cracked intracrystalline and intercrystalline boundaries that are abundant in the andesite (e.g., Figures 3 and 4). Many authors (e.g., Vinciguerra et al 2005;Keshavarz et al 2010;Blake et al 2012; Heap et al 2014) have also shown that the elastic wave velocities can be highly attenuated by the presence of microcracks.…”
Section: Micromechanical Interpretationmentioning
confidence: 99%
“…The development of microcracks during uniaxial compression, and the coalescence of these cracks (newly formed and pre-existing), leads to the failure of the sample (Brace et al 1966;Bieniawski 1967). In samples that already show relatively high crack densities, less energy is required to coalesce existing cracks and thus they are inherently weaker (David et al 1999;Ferrero and Marini 2001;Keshavarz et al 2010). By utilizing AE monitoring during our UCS testing, we observe that fewer events occur during uniaxial compression in weaker samples than those with higher strength (Figure 10), indicating that there are far more pre-existing cracks in the weaker samples (Hardy 1981;Eberhardt et al 1998;Nicksiar and Martin 2012).…”
Section: Micromechanical Interpretationmentioning
confidence: 99%
“…Many experimental studies have been conducted on different rocks, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] with an objective to observe and explain the behavior of physical and mechanical properties of these rocks under high temperature or after thermal treatment. All these experimental works are focus on sandstone [4][5][6][7], granite [1,[8][9][10], carbonates [2] and gabbro [11].…”
Section: Introductionmentioning
confidence: 99%
“…All these experimental works are focus on sandstone [4][5][6][7], granite [1,[8][9][10], carbonates [2] and gabbro [11]. However, few studies are interested on the gneiss rock microscopic analysis of thin section of the heated specimen.…”
Section: Introductionmentioning
confidence: 99%
“…1, the stress-strain curve of this part is usually non-linear (concave). In particular, when a specimen experiences a high degree of thermal loading, the initial stress-strain curve will be strongly non-linear (Rosengren and Jaeger 1968, Homand-Etienne and Houpert 1989, Mahmutoglu 1998, Du et al 2004, Keshavarz et al 2010. Because the nonlinearity is associated with Fig.…”
Section: Introductionmentioning
confidence: 99%